Tree Species Population Dynamics in the Tropical Dry Deciduous Forest of Gandhamardan Hills, Eastern Ghats, Western Odisha - Bhadra, A. K.; Pattanayak, S. K. (Indian Forester, 2019)
Eighty seven tree species were recorded in the present study. Seedling (A), sapling (B), bole (C), post bole (D), mature bole (E), tree (F) and mature tree (G) girth classes had 61, 75, 63, 47, 27, 13 and 14 species; while number of species found in any one, two, three, four, five, six and all seven girth classes were 18, 11, 14, 19, 15, 4, and 6 respectively. Six species present in all seven classes were Anogeissus latifolia, Lagerstroemia parviflora, Mitragyna parvifolia, Pterocarpus marsupium, Terminalia alata and Terminalia bellirica. The dominant tree population species were Diospyros melanoxylon in all the girth classes, A and E where as Anogeissus latifolia in B, Cleistanthus collinus in C and D; and Pterocarpus marsupium in F and G respectively. Only, seventeen species were available in both tree and mature tree classes. The per cent densities of all species populations in girth classes i.e. 54.94% (A), 25.76% (B), 9.52% (C), 5.86% (D), 2.25% (E), 0.92% (F) and 0.75% (G) formed sustainable upright pyramidal population structure at community level. However, no tree species showed upright structure individually making the tree community unsustainable at species level.